Optimization of the Selenization Pressure Enabling Efficient Cu2ZnSn(S, Se)4 Solar Cells. Issue 1 (16th November 2021) - Guo, Hongling; Meng, Rutao; Hu, Long; Lin, Chun-Ho; Sun, Yali; Liu, Yue; Wu, Jianyu; Shen, Zhan; Chu, Dewei; Wang, Gang; Wu, Li; Liang, Guangxing; et al.
Abstract : In spite of the merits such as Earth abundance and high performance, Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells suffer from unfavorable SnZn antisite defects and complexes, which act as nonradiative recombination centers and deteriorate the open‐circuit voltage ( V OC ). Therefore, the management of Sn composition is the prerequisite for achieving high‐efficiency CZTSSe photovoltaic devices. At present, the Sn‐related composition and defect modifications at different selenization pressures remain unclear, which restrain the development of efficient kesterite solar cells. Herein, a facile yet effective strategy to accurately adjust the Sn content in CZTSSe films by simply optimizing the selenization pressure is demonstrated. Compared with the widely used atmospheric pressure, it is unveiled that the appropriate negative pressure (0.7 atm) can tailor the optimal Sn content in the absorber layer, influencing both the Sn‐related defects and the microstructures. In contrast, a lower (0.4 atm) and a higher (1.3 atm) selenization pressure results in undesirable deep CuSn defects and a Sn(S, Se)2 secondary phase, respectively. A champion device fabricated at this optimal selenization pressure (0.7 atm) exhibits a power conversion efficiency of 11.32% with a V OC of 0.496 V. This study paves the path toward highly efficient kesterite solar cells by tailoring the composition‐dependent defects. Abstract : An efficient strategy is proposed to accurately adjust the Sn content and Sn‐related defects by tuning the selenization pressure from 0.4 to 1.3 atm. A champion device fabricated at the optimal selenization pressure (0.7 atm) exhibits a power conversion efficiency of 11.32% with a V OC of 0.496 V.